KERAGAMAN VESPIDAE PADA PERTANAMAN PALAWIJA DI KELURAHAN GURUN LAWEH KECAMATAN NANGGALO PADANG - -, Mardiwan - (Pendidikan Biologi, 2014)
The land cultivation has positive and negative impact for several of insect. The change type of plant after harvest give negative impact for insect and can cut life chain of insects. Related to that, it has been done research about varicosity Vespiade of palawija plant at Gurun Laweh District Nanggalo Valley Padang with the purpose to know the varicosity of vespidae in any types of palawija plant and physic-chemistry characteristic in any kinds of plantation of palawija in Gurun Laweh District Nanggalo Valley Padang. This research is done by survey descriptive method. The decision of the point in taking the sample is done by using purposive sampling technique. The taken Sample by insect net and identification of sample in Zoology Laboratorium STKIP PGRI SUMBAR. The Vespidae which found in Gurun Laweh District Nanggalo Valley Padang. is 56 insects with 6 types, they are Vespa avinis, V.tropica, V,bellicosa, V.multimacullata, rapalidia vasciata and Ropalidia sp. The similarities index of Vespidae in beans and chili are 67%. In chili and cucumber is 67%. Meanwhile in beans and cucumber really high. Similarities beans and cucumber are 100%. The average of temperature are 30,7-31,3 C. The average of air damp is 71,7-73%. The average of soil temperature is 27,7-28,1C and the average of soil pH is 6.